Penguatan Pendidikan Karakter Disiplin Melalui Kegiatan Ekstrakurikuler Pramuka di SD Islam Raudhatul Jannah - Aprilianti, Kurnia; Fitri, Lailatul; Salsabilla, Putri; Marwan, Syaiful (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This research focuses on how disciplined character can be instilled in scouts who are raised in scout extracurricular activities at Raudhatul Jannah Payakumbuh Islamic Elementary School. The purpose of this research is to describe the trainer's efforts in forming a disciplined character in students through scout activities at Raudhatul Jannah Payakumbuh Islamic Elementary School. This research was conducted at Raudhatul Janah Payakumbuh Islamic Elementary School involving 20 students who took part in scout raising and coaching activities. This type of research is qualitative research using three data collection techniques, namely interviews, observation and documentation. From the results of observations made, it shows that scout extracurriculars can form a disciplined character in students. The formation of this disciplined character can be formed due to the efforts made by the trainer by applying punishment methods and giving appreciation to students for PPB material and pioneering activities.